A stepwise dechlorination/cross-coupling strategy to diversify the vancomycin 'in-chloride'. Issue 3 (1st February 2016) - Wadzinski, Tyler J.; Gea, Katherine D.; Miller, Scott J.
Graphical abstract: Abstract: In an effort to rapidly access vancomycin analogues bearing diverse functionality at the 6c -Cl (the 'in-chloride') position, a two-step dechlorination/cross-coupling protocol was developed. Conditions for efficient cross-coupling of the relatively unreactive 6c -Cl group were found that ensure high conversion with minimal product decomposition. A set of 2c -dechloro-6c -functionalized vancomycin derivatives was prepared, and antibiotic activities of the compounds were evaluated against a panel of vancomycin-resistant and vancomycin-susceptible strains. Results from biological testing further underscore the steric sensitivity of vancomycin's binding pocket.